Haematological Evaluation of Albino Rats Fed with Pleurotus ostreatus Cultivated on Diverse Organic Substrates - Olabode, Olubusuyi Oladele; Akinnate, Felix Akindele; Bernard-Awe, Folakemi Elizabeth (Faculty of Natural and Applied Sciences Journal of Applied Biological Sciences, 2025)
This study evaluates the haematological impacts of Pleurotus ostreatus (oyster mushroom) cultivated on various substrates and integrated into the diets of albino rats (Rattus norvegicus). Using a controlled six-week feeding trial, sixty-three Sprague Dawley rats were grouped and administered diets incorporating P. ostreatus cultivated on compost and vermicompost substrates derived from different animal manures and lignocellulosic materials. Standard haematological indices—PCV, ESR, RBC, WBC, Hb, and differential WBC counts—were assessed post-trial to determine physiological responses. Results indicated substrate-specific variations in blood parameters. Notably, rats fed mushrooms cultivated on poultry droppings exhibited elevated RBC and Hb levels, suggesting improved erythropoiesis, while goats' dung substrates correlated with higher WBC counts, potentially reflecting immunomodulatory effects. The control group, which did not consume mushroom-infused diets, showed comparatively lower haematological values. These findings underscore the influence of cultivation substrate on the nutritional and therapeutic properties of P. ostreatus, with implications for its application in functional animal feed development. Further research is recommended to elucidate the biochemical mechanisms driving these effects.